1990
DOI: 10.1073/pnas.87.15.5950
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Pneumocystis carinii pneumonia with 1,3-beta-glucan synthesis inhibitors.

Abstract: Pneumocystis carini pneumonia is a major cause of death in AIDS patients in the United States. The presently available treatments have limited use due to a high incidence of adverse reactions. Therefore, there is an urgent need for a safer method for treatment and prevention of this disease. Recent evidence has suggested that P. carinn is related to fungi and that the wall ofthe cyst form contains 1,3-13-glucan as a major constituent. Based on this, several proposed 1,3-f3-glucan synthesis inhibitors were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
102
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(107 citation statements)
references
References 33 publications
5
102
0
Order By: Relevance
“…Cell extracts were prepared from mutant and wild-type cells grown to logarithmic phase as previously described (23). Assays of 1,3-␤-glucan synthase (8,43) and chitin synthase (24) were performed as previously described (16). A published procedure (23) for the preparation of soluble and insoluble membrane fractions was used.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell extracts were prepared from mutant and wild-type cells grown to logarithmic phase as previously described (23). Assays of 1,3-␤-glucan synthase (8,43) and chitin synthase (24) were performed as previously described (16). A published procedure (23) for the preparation of soluble and insoluble membrane fractions was used.…”
Section: Methodsmentioning
confidence: 99%
“…Nikkomycins and polyoxins are competitive inhibitors of chitin synthases (7,10,11,18). Papulacandin B (2,30,43,48), aculeacin A (29,49), echinocandin B (46), and pneumocandin B 0 (6) inhibit synthesis of 1,3-␤-glucan, most likely by inhibiting activity of 1,3-␤-glucan synthase. The killer toxin of Hansenula mrakii kills sensitive strains of S. cerevisiae by inhibiting 1,3-␤-glucan synthase activity (25,50).…”
mentioning
confidence: 99%
“…To accomplish this, we employed the rat Pc pneumonia model that has been used extensively to analyze drug activity against the organism (6,60,61). Due to limited drug supply, we treated the rats with nikkomycin Z by oral gavage after establishment of fulminate PCP by immune suppressing rats with corticosteroids and inoculating with Pc.…”
Section: Efficacy Of the Inhibitor Nikkomycin Z In The Rat Model Ofmentioning
confidence: 99%
“…Other fungi such as Aspergillus nidulans and Candida albicans alter gene expression as an adaptive response to environmental pH changes in order to maintain cell wall integrity and promote viability under various conditions (6,11,21,23,(32)(33)(34)(35). Specifically, it has been demonstrated that C. albicans expresses a unique family of pH-regulated genes required for virulence.…”
mentioning
confidence: 99%